PROFESSIONAL CAREER SUPPORT TEACHER-PSYCHOLOGIST - Dombek, Svetlana; Lebedeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article deals with the problem of professional development of a psychologist's career in education. The authors of the article clarify the concept of «professional career»; identify the necessary and sufficient organizational and managerial conditions for supporting the professional career of a teacher-psychologist; conclude that the development of auto psychological competence in teachers-psychologists at the stage of professional adaptation is relevant.Analysis of the results of the study showed that young educational psychologists are focused on professional self-development, but they need competent support for their professional career. The authors describe the experience of practical implementation of organizational and managerial conditions for supporting the professional career of a teacher-psychologist, and note the positive dynamics of the participants ' readiness to build a professional career.The article is intended for public reading, as well as for those who are interested in psychological and pedagogical research.